Porcine congenital splayleg: a review - Ooi, Peck Toung; Tee, Tuan Poy; Lai, Jyh Mirn (Veterinary Association Malaysia, 2012)
Porcine congenital splayleg (PCS) is a clinical condition of newborn piglets, characterised by muscle weakness, resulting in the inability to properly stand and walk, with affected limbs extended sideways or forwards. It is arguably the most important congenital defect of commercial piglets and causes significant economic loss to pig farmers. The aetiology and pathogenetic mechanisms for PCS are still not well understood. Various management, nutrition and genetic factors have been found associated with PCS problems, but the actual cause remain obscure. Proper management and good farm practise are essential to control this multi-factorials PCS problem.